Euler equation estimation: Children and credit constraints - Thomas Høgholm Jørgensen (Quantitative Economics, 2016)
Conventional estimators based on the consumption Euler equation, intensively used in studies of intertemporal consumption behavior, produce biased estimates of the effect of children on the marginal utility of consumption if consumers face credit constraints. As a more constructive contribution, I propose a tractable approach to obtaining bounds on the effect of children on the marginal utility of consumption. I estimate these bounds using the Panel Study of Income Dynamics and find that conventional estimators yield point estimates that are above the upper bound. Children might, thus, not increase the marginal utility of consumption as much as previously assumed.
Keywords: D12; D14; D91; 330; Consumption; Euler equation estimation; credit constraints; children; demographics; life cycle; bounds